Improved minimal residual disease detection by targeted quantitative polymerase chain reaction in Nucleophosmin 1 type a mutated acute myeloid leukemia. Issue 10 (24th June 2016) - Pettersson, Louise; Levéen, Per; Axler, Olof; Dvorakova, Dana; Juliusson, Gunnar; Ehinger, Mats
Abstract : Multicolor flow cytometry (MFC) and real‐time quantitative PCR (RQ‐PCR) are important independent techniques to determine minimal residual disease (MRD) in acute myeloid leukemia (AML). MFC is the standard method, but may be unreliable. Therefore, MFC‐based determination of MRD with an RQ‐PCR‐based approach targeting the nucleophosmin 1 ( NPM1 ) type A mutation was set out to compare. Since most current NPM1 RQ‐PCR MRD protocols suffer from clear definitions of quantifiability, we sought to define quantifiability in a reproducible and standardized manner. The limit of quantifiability of our RQ‐PCR protocol for the NPM1 type A mutation varied between 0.002% and 0.04% residual leukemic cells depending on the features of the standard curve for each PCR experiment. The limit of detection was close to 0.001% leukemic cells. The limit of detection by MFC ranged from 0.01% to 1% depending on the phenotype of the leukemic cells as compared with non‐leukemic bone marrow cells. Forty‐five MRD samples from 15 patients using both NPM1 mutation specific RQ‐PCR and MFC were analyzed. In 32 of the 45 samples (71%), an MRD‐signal could be detected with RQ‐PCR. A quantifiable NPM1 mutation signal was found in 15 samples (33%) (range 0.003%–2.6% leukemic cells). By contrast, only two follow‐up samples (4%) showed residual leukemic cells (0.04% and 0.3%, respectively) by MFC. Thus, RQ‐PCR of the NPM1 type A mutation was more sensitive and reliable than MFC for determination of MRD, which might have clinical implications. © 2016 Wiley Periodicals, Inc.